1994
DOI: 10.1038/bjc.1994.426
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 5-fluorouracil and alpha interferon and 5-fluorouracil and leucovorin on cellular anti-tumour immune responses in patients with advanced colorectal cancer

Abstract: SaryInterferon (IFN-a) enhances the activity of 5-fluorouracil (5-FU) in the treatment of advanced colorectal cancer although the mechanism is not understood. We have investigated the effect of this combination on cellular immunity and compared this with standard therapy of 5-FU/L-leucovorin, in Poon et al., 1989).The mechanism by which IFN-a modulates the activity of 5-FU is unknown. In vitro cytoxicity studies using gastrointestinal cell lines how that interferon acts synergistically with 5-FU (Wadler et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…GSEA revealed that the ATG signature included genes that were robustly involved in multiple immune/ in ammatory pathways including IL6/JAK/STAT3, IL2/STAT5, IFN-α, IFN-γ, TNF-α/NF-κB, and the in ammatory response presented a particular relation to CRC proliferation or prognosis as previous studies revealed [21][22][23][24][25]. As our ndings suggested that a high autophagy risk score correlated with the downregulation of these immune/ in ammatory pathways, we speculated that autophagy might play a role in CRC tumorigenesis and tumor proliferation via an anti-immune/ anti-in ammatory response.…”
Section: Discussionmentioning
confidence: 61%
“…GSEA revealed that the ATG signature included genes that were robustly involved in multiple immune/ in ammatory pathways including IL6/JAK/STAT3, IL2/STAT5, IFN-α, IFN-γ, TNF-α/NF-κB, and the in ammatory response presented a particular relation to CRC proliferation or prognosis as previous studies revealed [21][22][23][24][25]. As our ndings suggested that a high autophagy risk score correlated with the downregulation of these immune/ in ammatory pathways, we speculated that autophagy might play a role in CRC tumorigenesis and tumor proliferation via an anti-immune/ anti-in ammatory response.…”
Section: Discussionmentioning
confidence: 61%
“…GSEA revealed that the ATG signature included genes that were robustly involved in multiple immune/inflammatory pathways including IL6/JAK/STAT3, IL2/STAT5, IFN-α, IFN-γ, and TNF-α/NF-κB, and the inflammatory response presented a particular relation to CRC proliferation or prognosis as previous studies revealed ( Nichols et al, 1994 ; Eguchi et al, 2003 ; De Simone et al, 2015 ; Park et al, 2017 ; Giordano et al, 2019 ). As our findings suggested that a high autophagy risk score correlated with the downregulation of these immune/inflammatory pathways, we speculated that autophagy might play a role in CRC tumorigenesis and tumor proliferation via an anti-immune/anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 78%
“…GSEA revealed that the ATG signature included genes that were robustly involved in multiple immune/ in ammatory pathways including IL6/JAK/STAT3, IL2/STAT5, IFN-α, IFN-γ, TNF-α/NF-κB, and the in ammatory response presented a particular relation to CRC proliferation or prognosis as previous studies revealed [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 90%